Lacosamide as an Adjunctive Therapy in Drug-Resistant Absence Epilepsy: Successful Treatment of Four Patients - Moosavian, Toktam; Moosavian, Hamidreza (Iranian Journal of Child Neurology, 2024)
Absence epilepsy is one of the most common epileptic syndromes in children, and despite its benign nature, a percentage of these children are drug-resistant. This study presents four cases of drug-resistant absence epilepsy in children who were unresponsive to traditional antiepileptic drugs. The study reports the successful use of Lacosamide as an adjunctive therapy to completely control symptoms and electroencephalogram (EEG) abnormalities. The patients, aged four to ten years, had previously failed treatment with Ethosuximide, Sodium Valproate, Levetiracetam, and Topiramate in various combinations. Lacosamide was initiated at a dose of 10 mg/kg per day in combination with Sodium valproate, resulting in rapid and sustained improvement. The patients remained symptom-free and showed no EEG abnormalities for one to two years. These findings suggest that Lacosamide can be considered a safe add-on drug for refractory absence epilepsy. However, it may be contended that additional confirmatory trials are necessary to investigate the effects of Lacosamide in a larger patient population